Factors Influencing Public Awareness of and Attitudes Toward Palliative Care: A Cross-Sectional Analysis of the 2018 HINTS Data - Lu, Xinyu; Liu, Jiawei (Frontiers in Public Health, 2022)
Background The global burden of serious health-related suffering requiring palliative care has been projected to grow significantly by 2060, which indicates the imminent need for integrating palliative care into health systems globally. Moreover, research evidence has been accumulating in support of the earlier adoption of palliative care into the treatment course of serious life-threatening illnesses. However, barriers to earlier access to palliative care still remain, which might be attributable to the global lack of awareness of palliative care and the prevalence of negative perceptions and attitudes. To address this, further investigation of the influencing factors of public perceptions of palliative care is imperative to help inform and develop effective targeted public health campaigns and education messages aimed at improving views of palliative care and thereby early access. Methods We used data from the Health Information National Trends Survey (HINTS), a nationally representative cross-sectional survey routinely administrated by the National Cancer Institute from the United States. Specifically, we analyzed the latest palliative care data from HINTS 5 Cycle 2 data set. Sociodemographic characteristics, individual factors such as self-perceived health status, and interpersonal factors such as relationship quality were examined as predictors of public awareness of and attitudes toward palliative care. Survey data were analyzed using SPSS 26 with multiple hierarchical regression tests. Results Results showed that people's quality of interpersonal relationships was a significant influencing factor of their awareness of and attitudes toward palliative care. Moreover, cancer diagnosis history and perceived healthcare quality were found to jointly affect their awareness of palliative care; perceived health status and patient centeredness interacted to influence their awareness of and attitudes toward palliative care. Finally, female, non-white, and poorer people were more aware of palliative care, while female and more educated people had more favorable attitudes. Conclusions The quality of social relationships emerges as a significant predictor of people's awareness of and attitude toward palliative care, as treatment options and decisions of serious life-threatening illnesses often involve the patients' family. The results hold strong implications for public health campaigns and education messages aiming at changing people's views of palliative care, which ultimately improve end-of-life outcomes.